Peran gaya kepemimpinan transformasional, perilaku kewargaan organisasional, dan stres kerja terhadap turnover intention - Gabrielle Tania Suhardi; Mei Ie (Jurnal Manajemen Maranatha, 2023)
The purpose of this study is to determine the effect of transformational leadership, organizational citizenship behavior, and work stress on employee turnover intention at PT XYZ.  Researchers distributed questionnaires to employees at PT XYZ totaling 50 respondents using the purposive sampling method.  Data analysis using Structural Equation Modeling (SEM)-SmartPLS. This research suggests that transformational leadership style and organizational citizenship behavior negatively affect employee turnover intention, while work stress positively affects employee turnover intention at PT XYZ. The implication of this study is that companies are expected to control employee turnover rates through the application of appropriate leadership styles, encourage employee awareness to improve their organizational citizenship behavior, and also maintain employee stress levels so that company activities can run well.